2018
DOI: 10.1002/ejic.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition to SnII Guanidinate Complexes: Precursors to Tin(II) Chalcogenide Nanocrystals

Abstract: SnS, SnSe and SnTe are potentially important semiconductor materials. Here, we describe the application of chalcogen containing SnIV guanidinate precursors for the production of tin(II) chalcogenide nanocrystals. Reaction of the stannylene(II) guanidinate complex [{Me2NC(NCy)2}2Sn] (1) with Ph2E2 (E = S, Se, Te), and CBr4 forms the SnIV complexes [{Me2NC(NCy)2}2Sn(Ch‐Ph)2] (2–4) and [{Me2NC(NCy)2}2SnBr2] (5), respectively. Complex 5 has been subsequently used for the synthesis of the corresponding SnIV mono ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
3
17
0
2
Order By: Relevance
“…A previous study on Sn­(IV) bis-guanidinate chalcogenide complexes observed a similar conversion of Sn­(IV) to Sn­(II) and a loss of Te(0) during the thermal decomposition process around 130 °C . The process produced SnTe nanocrystals with high controllability on the +2 oxidation state of Sn . The absence of SnTe 2 phase in the phase diagram of Sn-Te solid solution further supports the deposition of SnTe instead of SnTe 2 .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…A previous study on Sn­(IV) bis-guanidinate chalcogenide complexes observed a similar conversion of Sn­(IV) to Sn­(II) and a loss of Te(0) during the thermal decomposition process around 130 °C . The process produced SnTe nanocrystals with high controllability on the +2 oxidation state of Sn . The absence of SnTe 2 phase in the phase diagram of Sn-Te solid solution further supports the deposition of SnTe instead of SnTe 2 .…”
Section: Resultssupporting
confidence: 61%
“…The intended ligand exchange reaction for the growth of SnTe films is described below. The SnTe deposition requires the electron transfer from Te 2– to Sn­(IV) and sufficient purging of the Te(0) element. A previous study on Sn­(IV) bis-guanidinate chalcogenide complexes observed a similar conversion of Sn­(IV) to Sn­(II) and a loss of Te(0) during the thermal decomposition process around 130 °C . The process produced SnTe nanocrystals with high controllability on the +2 oxidation state of Sn .…”
Section: Resultsmentioning
confidence: 59%
“…Depending on the π‐accepting properties of stannylenes, the tin‐selenium bond can be described via two resonance forms: i) as a Sn=Se double bond (strong π‐acceptor, deshielded selenium, downfield shift) and ii) as a Sn + −Se − single bond with partial charges (weak π‐acceptor, shielded selenium, upfield shift). [Li 2 (thf) x ][2‐Se] shows a 77 Se NMR shift of −391.99 ppm, lying in a range comparable to a tetracoordinated but neutral, bis amidinato stanna(II) selenido complex—thus no notable strong upfield shift [29] . An explanation for this seemingly contrasting result with the TEP number was required.…”
Section: Resultsmentioning
confidence: 99%
“…Bemerkenswerterweise liegt dieser Wert unter dem aller bisher beschriebenen Carbene (einschließlich CAACs) [2b] und der elektronenreichsten Phosphinliganden, [27] was die σ-Donor-und schwachen π-Akzeptoreigenschaften von 77 Se-NMR-Verschiebung von À 391.99 ppm, welche in einem für neutrale, tetrakoordinierte Bis(amidinato)stana(II)selenidokomplexe vergleichbaren Bereich liegt -also keine nennenswert starke Hochfeldverschiebung darstellt. [28] Eine Erklärung für dieses scheinbar widersprüchlichen Ergebnis mit dem TEP-Wert war erforderlich. Im Jahr 2020 berichteten Bertrand und Mitarbeiter über Carben-Selenid-Addukte mit unerwartet tieffeldverschobenen 77 Se-NMR-Resonanzen, welche durch nicht-klassische C(sp 3 )HÀ Se-Wasserstoffbrücken verursacht werden.…”
Section: Forschungsartikelunclassified
“…Im Jahr 2020 berichteten Bertrand und Mitarbeiter über Carben-Selenid-Addukte mit unerwartet tieffeldverschobenen 77 Se-NMR-Resonanzen, welche durch nicht-klassische C(sp 3 )HÀ Se-Wasserstoffbrücken verursacht werden. [29] [28,30] Interessanterweise wurde gezeigt, dass dianionische Calix- [4]pyrrolatokomplexe von Ni II und Cu II ausschließlich als η 5koordinierende Sechseleketronendonoren über ihre Pyrrolatoeinheiten wirken, die in ihrer zweiten Koordinationssphäre polymetallische Sandwichkomplexe bilden, während der σ-Donormodus nur für [2] 2À beobachtet wird. [13d, 31] Die oxidative Addition von Kohlenstoff-Halogen-Bindungen stellt einen üblichen Reaktivitätsmodus für niedervalente Hauptgruppenelementverbindungen, einschließlich der klassischen Stannylene, dar.…”
Section: Forschungsartikelunclassified